Wind Energy Conversion Systems Based On a DFIG Controlled By Indirect Vector Using PWM And SVM - Naim Cherfia; Djallel Kerdoun (Institute of Advanced Engineering and Science, 2016)
A well-prepared abstract enables the reader to identify the basic content of a document quickly and accurately,). This work presents consideration and use of the asynchronous generator in the production of wind energy. To do this, a model of the wind turbine has been established, the mathematical model of the doubly fed induction generator (DFIG) variable speed is presented and the control quantities used when integrated with a wind system. A modeling in a diphasic reference mark related to the stator field and a strategy vector control active and reactive power are offered with a PWM and SVM technique for inverter control is considered in our work.